The goose that laid the rotten egg : a graphic novel - Foxe, Steve (Far out fables, 2021)
In this graphic novel version of Aesop's "The Goose that Laid the Golden Egg," a young girl named Val helps a wounded (and gassy) goose and is rewarded with golden eggs, but when Val's greedy relatives abuse the goose, they are rewarded with a different type of egg. Includes a classic retelling of the fable, visual questions, and a glossary.